Finding Joy in Communication with Families - Teichert, Laura; Chan, Valerie (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2025)
Family engagement is a strong predictor of children’s academic success and communication is a key component of engagement (McWayne et al., 2016). Yet, little research has focused on families’ and schools’ communication practices. Using a lens of literacy as a social practice, communication is described as social and cultural and not a universal skill-set. That at a basic level, literacy is effective communication. This inquiry focused on the three K-12 teachers and considers the joyful opportunities afforded in their home-school communication. By engaging in Narrative Inquiry, we unravel the participant teachers’ experiences and preferences in communicating with families through a lens of joy and consider the barriers faced when maintaining joy. Key moments of joy were sparked when providing positive communication, developing systems/strategies for continual communication, and in building relationships.